Industrial respirators and their impact on cases of infectious infections in the hospitals in Mecca during the Hajj season - Muhannad Ali Alqahtani, Rawan Mansour Kamrig, Majed Tariq Iskandarani, Mishari Fahad Al-Ghamdi, Mutlaq Dhafer Al-Zulaiq,Ahmad Ali Althaqafi, MAJED MENWER NAWER ALL AHYANI; AHMAD FAHAD ALRASHDI, Saad Mohammed Al-Shahri , Riyadh saleh Alzahrani (Journal of International Crisis and Risk Communication Research, 2024)
Background The annual Hajj pilgrimage to Mecca involves millions of participants, creating a high-risk environment for respiratory infections among patients and healthcare workers (HCWs). Crowded conditions, prolonged exposure, and variable compliance with infection control measures amplify the risk of hospital-acquired re spiratory infections (HARI). Despite global recommendations for protective interventions like respirators, their real-world effectiveness in high-risk settings like the Hajj remains underexplored. Patients and Methods A prospective cohort study was conducted involving 482 patients and 195 HCWs in hospitals during the Hajj period. Data collection included patient demographics, clinical features, pathogen identification, and HCW compliance metrics for respirator use. Environmental monitoring of air quality and microbial loads was performed across different hospital zones. Statistical analysis included descriptive statistics, chi-square tests, and logistic regression to assess the association between respirator compliance and infection outcomes. Results Among patients, the HARI rate was 17.6%, predominantly viral (9.3%), with an average onset of 5.2 ± 1.4 days. Mild cases accounted for 59.1% with an average symptom duration of 5.2 ± 1.3 days, while severe cases showed a duration of 12.6 ± 3.2 days. HCW infection rates decreased from 23.1% to 9.2% (60.2% reduction) post-intervention. Respirator compliance showed a gradual decline over four weeks (92.3% to 83.2%). Environmental monitoring revealed higher microbial loads in high-traffic areas like emergency rooms (342 ± 52 CFU/m³) compared to ICUs (112 ± 21 CFU/m³). Extended shift hours (OR 2.45, p < 0.001) and improper respirator fit (OR 1.76, p = 0.003) were significant risk factors for non-compliance. Conclusion The study highlights the critical role of respirators in reducing HARI among HCWs and patients during the Hajj. However, challenges such as declining compliance, environmental microbial loads, and risk factors like extended shifts necessitate targeted interventions. Enhanced vaccination, regular respirator replacement, and robust environmental controls are recommended to optimize infection prevention in high-risk mass gatherings.